Determinants of purchase intention and attitudes toward organic food in Myanmar: The role of sociodemographic characteristics - Htar, May Thet; Myint, Theingi; Moh, Moh; Soe, Thi Thi; Hnin, Chu Htet; Aye, Htet Marlar; Aye, Yin Nyein (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2022)
Organic farming and organic food market have been growing around the world for many years. In Myanmar, organic food is in the early stage for production and marketing. The study aims to analyse the determinants of the consumers’ purchase intention and attitudes toward organic food and the role of sociodemographic characteristics. The data was collected from 80 consumers of Nay Pyi Taw Region using structured questionnaires. The findings indicated that 38 percent of the respondents perceived that they were fully aware of organic food, organic agriculture and their differences with conventional food and agriculture. Among the respondents, 61 percent were willing to pay premium price for organic food. The results indicated that age and household size of the respondents were not significantly associated with the respondents’ awareness level of organic food, purchase intention, the premium price the respondents were willing to pay, expected consumption frequency in the future and checking before buying while these variables were positively associated with the education level of the respondents. These variables were also significantly different according to the respondents’ occupation types and residential places. Regression analysis predicted that the respondents’ income, ratio of food expense and income, education level, awareness level of organic food and the premium price they are willing to pay have significant impacts on their purchase intention in the future. The findings from this study contributed the importance of the respondents’ sociodemographic characteristics on purchase intention and attitudes toward organic food for further research.